DEVONIAN NERVOSTROPHIINAE (STROPHOMENIDA, BRACHIOPODA) OF THE RUSSIAN PLATFORM - Alekseeva R.E. (My University, 2003)
Results of the revision of the taxonomic composition of Nervostrophiinae from the Devonian of the Russian Platform based on the A.I. Ljaschenko memorial collection are presented. Three new genera and seven new species belonging to the subfamily Nervostrophiinae Harper et Boucot, 1978 have been designated. The generic designation of all species known in the area under study has been revised.
Keywords: Devonian; Paleozoic::Devonian; Палеозой::Девонская